A Narrative Review on the Impact of Digital Pedagogy on Psychological Wellbeing of Students during Global Pandemic - Kritika Chaudhary; Chehak Gidwani (Progress in Language, Literature and Education Research Vol. 9, 2024)
Background: The COVID-19 pandemic has gravely impacted the education system across the world. The imposition of the worldwide lockdown in order to prevent the spread of the deadly virus has led to the unprecedented shutting down of educational institutions. The UNESCO report suggests that nearly 90% of the student population has been hit by coronavirus during the month of April 2020. The migration of the teaching learning process to online mode during the pandemic has posed a plethora of difficulties and challenges for young students across the world. It highlights the difficulties faced by students and the stress on the education system during times of medical health emergencies and lockdown situations in the past. The primary objective of this study is to undertake a narrative review of studies assessing the impact of the lockdown crisis on student well-being and education. Methods: Keyword searches of PubMed and Google Scholar databases led to the identification of 25 studies for the present review. Results: Studies (n = 25) exploring the students’ experience of lockdown and the impact of pandemic situations on their education were identified. Analysis of the results of these studies revealed the following main themes: Impact on students’ mental health, causes of deteriorated mental health of students: multiple heterogeneous stressors, socio-economic divide in education, gendered impact of epidemics and impact on the educational system: challenges of e-learning. Conclusion: Lockdown situations not only disrupt the normal study routine of students and cause a slowdown in their learning curve, it also creates a significant mental burden causing adverse impacts on their mental health. The lack of appropriate technological devices and the lack of sufficient internet bandwidth has deepened the educational divide. Remote education systems have proven inadequate in replicating the chalk-and-talk methodologies of teachers. The study suggested future direction including teachers should be professionally trained and motivated to upgrade their pedagogy to meet the demands arising from the shift to online education.